Superconducting dome associated with the suppression and re-emergence of charge density wave states upon sulfur substitution in CuIr2Te4 chalcogenides. (18th May 2022) - Boubeche, Mebrouka; Wang, Ningning; Sun, Jianping; Yang, Pengtao; Zeng, Lingyong; Luo, Shaojuan; He, Yiyi; Yu, Jia; Wang, Meng; Cheng, Jinguang; Luo, Huixia
Abstract: We report the path from the charge density wave (CDW)-bearing superconductor CuIr2 Te4 to the metal insulator transition (MIT)-bearing compound CuIr2 S4 by chemical alloying with the gradual substitution of S for Te. The evolution of structural and physical properties of the CuIr2 Te4− x S x (0 ⩽ x ⩽ 4) polycrystalline system is systemically examined. The x-ray diffraction (XRD) results imply CuIr2 Te4− x S x (0 ⩽ x ⩽ 0.5) crystallizes in a NiAs defected trigonal structure, whereas it adapts to the cubic spinel structure for 3.6 ⩽ x ⩽ 4 and it is a mixed phase in the doping range of 0.5 < x < 3.6. Unexpectedly, the resistivity and magnetization measurements reveal that small-concentration S substitution for Te can suppress the CDW transition, but it reappears around x = 0.2, and the CDW transition temperature enhances clearly as x augments for 0.2 ⩽ x ⩽ 0.5. Besides, the superconducting critical temperature ( T c ) first increases with S doping content and then decreases after reaching a maximum T c = 2.82 K for CuIr2 Te3.85 S0.15 . MIT order has been observed in the spinel region (3.6 ⩽ x ⩽ 4) associated with T MI increasing with x increasing. Finally, the rich electronic phase diagram of temperature versus x for this CuIr2 Te4− x S x system is assembled, where the superconducting dome is associated with the suppression and re-emergence of CDW as well as MIT states at the end upon sulfur substitution in the CuIr2 Te4− x S x chalcogenides.